Guidance, Navigation and Control Conference 1989
DOI: 10.2514/6.1989-3428
|View full text |Cite
|
Sign up to set email alerts
|

A design procedure for the handling qualities optimization of the X-29A aircraft

Abstract: A design technique for handling qualities improvement was developed for the X-29A aircraft. As with any new aircraft, the X-29A control law designers were presented with a relatively high degree of uncertainty in their mathematical models. The presence of uncertainties, and the high level of static instability of the X-29A caused the control law designers to stress stability and robustness over handling qualities. During flight test, the mathematical models of the vehicle were validated or corrected to match t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Thus, as discussed in detail in Ref. 21, initial flight tests of the X-29 handling qualities indicated that the aircraft characteristics were Level 2 (adequate). The main deficiency reported by the pilots was sluggishness in the pitch axis.…”
Section: A X-29a Design Methods and Flight Test Experiencementioning
confidence: 96%
See 2 more Smart Citations
“…Thus, as discussed in detail in Ref. 21, initial flight tests of the X-29 handling qualities indicated that the aircraft characteristics were Level 2 (adequate). The main deficiency reported by the pilots was sluggishness in the pitch axis.…”
Section: A X-29a Design Methods and Flight Test Experiencementioning
confidence: 96%
“…The wing-canard planform results in a high level of instability that has a time-to-double amplitude near 150 msec. 21 There exist both low-and.…”
Section: X-29 High Performance Fixed-wing Aircraft Control Law Designmentioning
confidence: 98%
See 1 more Smart Citation